2011
DOI: 10.1111/j.1600-0625.2011.01260.x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of tumor-infiltrating Foxp3+ T-cell subpopulations in metastatic melanoma

Abstract: Regulatory T cells have already been associated with poor prognosis in various types of cancer. It was previously reported, in ovarian carcinoma, that quantification of Foxp3 identified a subgroup of patients characterized by a significantly worse prognosis in terms of overall survival (OS) and progression‐free survival (PFS), suggesting that high expression levels of Foxp3 might represent a surrogate marker for an immunosuppressive microenvironment contributing to tumor immune escape. The main objective of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 31 publications
2
30
0
Order By: Relevance
“…[20][21][22][23][24][25] In contrast, a high infiltration of Tregs has been reportedly associated with an improved OS in colorectal cancer. 26 Although FOXP3 expression has been used as a specific marker of Tregs, 27 FOXP3-positive cells were revealed to include cells heterogeneous in both phenotype and function.…”
Section: Discussionmentioning
confidence: 95%
“…[20][21][22][23][24][25] In contrast, a high infiltration of Tregs has been reportedly associated with an improved OS in colorectal cancer. 26 Although FOXP3 expression has been used as a specific marker of Tregs, 27 FOXP3-positive cells were revealed to include cells heterogeneous in both phenotype and function.…”
Section: Discussionmentioning
confidence: 95%
“…Intratumoral Treg prevalence has been shown to be an independent negative prognostic marker for uveal melanoma [30]. Knol et al [24] showed that Tregs decrease progression free survival in allsite metastatic melanoma. The prognostic significance of IDO immunoreactivity in addition to metastasis has also been shown in SLNs of 160 patients in all-site melanoma by Speeckaert et al [31].…”
Section: Discussionmentioning
confidence: 98%
“…Staining for CD3 and CD4 was also initially performed to confirm that the FoxP3+ cells represented T cells, rather than another FoxP3+ cell type. FoxP3 positivity alone has previously been used as the most specific marker of Tregs [15,[24][25][26].…”
Section: Methodsmentioning
confidence: 99%
“…The presence of a high number of Tregs in a variety of malignancies has been correlated with poor prognosis (such as melanoma, ovarian carcinoma and Ewing sarcoma) [17][18][19] or favorable prognosis (colorectal adenocarcinoma) [20]. Furthermore, there seems to be a stage-related increase of Treg density [21].…”
Section: Tregs Can Be Recruited Multiplied and Converted In The Tumomentioning
confidence: 98%